Scenario Planning Application of Onion Warehouse Receipt System (SRG) in Sumbawa Regency - Deny Armansyah (Institut Pemerintahan Dalam Negeri (IPDN), 2020)
This study aims to determine and analyze the Scenario Planning Application of the Shallot Warehouse Receipt System (SRG) in Sumbawa Regency using the concept of scenario planning from Lindgren and Hans (2003) as well as analyzing supporting and inhibiting factors using the concept of Yunus (2016) combined with David's concept (2009). This research uses qualitative research methods. Data collection techniques used are interviews, observation, and documentation. The results of this study indicate that, the implementation of the Warehouse Receipt System has received a positive response, both from the Stakeholders, and the Shallot farmers themselves, but to implement this warehouse receipt system there are still some obstacles such as storage warehouse facilities, CAS (Controlled Atmosphere Storage) facilities , Availability of Supporting Regulations, SRG Human Resources Managers, Access to information to Onion Farmers So that in this study two scenarios are found that are in accordance with the problems in the study. Scenario A and Scenario B, where the Stakeholder and Shallot Farmers are in a positive condition in Scenario A , and in Scenario B Stakeholders are in a positive condition and Farmers in a negative condition. Based on this analysis, the authors conclude several things that Stakeholders must do. In Scenario A, Local Government Stakeholders and DPRD must immediately Cooperate immediately with the banks which are marked by the signing of a Memorandum of Understanding (MoU), make regulations, improve the quality of human resources, especially SRG managers, prepare supporting infrastructure such as land or land that is to become a warehouse construction site, then in Scenario B stakeholders can improve the quality of SRG Bage tango personnel, prepare supporting infrastructure in the form of CAS machines and warehousing facilities, carry out a gradual outreach to onion farmers, increase promotion of the ease of the issuance of warehouse receipts as credit guarantees, increase awareness of onion farmers about the security of transactions in warehouse receipts compared to conventional methods.